Ghost hands : a story inspired by Patagonia's Cave of the Hands - Barron, T. A.; Low, William (New York : Philomel Books, 2011)
Auki, a young member of the Tehuelche tribe in Patagonia, wants to prove himself as a hunter but when he sets out on his own to face the puma, he stumbles upon a sacred cave and its guardian.
Kirkus Review
Kirkus Review, May 2011
2.3
K-3
K-3
Keywords: Cave paintings -- Juvenile fiction; Courage -- Juvenile fiction; Indians of South America -- Argentina -- Juvenile fiction; Tehuelche Indians -- Juvenile fiction; Cave paintings -- Fiction; Courage -- Fiction; Indians of South America -- Argentina -- Fiction; Tehuelche Indians -- Fiction; Cave drawings and paintings -- Fiction; Courage -- Fiction; Native Americans -- Argentina -- Fiction; Tehuelche Indians -- Fiction; Patagonia (Argentina and Chile) -- History -- Juvenile fiction; Patagonia (Argentina and Chile) -- History -- Fiction; Patagonia (Argentina and Chile) -- History -- Fiction; Picture books for children